2022
DOI: 10.1177/10556656221106881
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cleft lip and/or Palate Prevalence at Birth in Mexico: A National (Ecological) Study Between 2003 and 2019

Abstract: Objective To describe trends in cases and prevalence at birth rates of cleft lip and/or palate (CL/P) in Mexico between 2003 and 2019. Design Ecological study. Setting Multiple data sources systematically collected into a national epidemiological surveillance data warehouse. Participants National Live Birth Information System. Main Outcome Measure(s) Both cases and prevalence at birth rates of CL/P in Mexico within a 17-year period were used as dependent variables. Results At the national level there were 23 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
0
1
Order By: Relevance
“…The prevalence of CL ± P in Mexico has previously been reported as 0.53 per 1000 live births, which is slightly higher than the global prevalence; however, it has previously been described that prevalence varies from country to country and that this variation may be secondary to racial, environmental, and cultural diversity 2,10 . Previously, Ceron-Zamora et al reported that Hidalgo and Jalisco were the states with the highest prevalence; however, in our study, most patients came from the State of Mexico, Mexico City, and Guerrero, while <10% of patients were from the state of Hidalgo, and no patients were referred from Jalisco.…”
Section: Discussioncontrasting
confidence: 64%
“…The prevalence of CL ± P in Mexico has previously been reported as 0.53 per 1000 live births, which is slightly higher than the global prevalence; however, it has previously been described that prevalence varies from country to country and that this variation may be secondary to racial, environmental, and cultural diversity 2,10 . Previously, Ceron-Zamora et al reported that Hidalgo and Jalisco were the states with the highest prevalence; however, in our study, most patients came from the State of Mexico, Mexico City, and Guerrero, while <10% of patients were from the state of Hidalgo, and no patients were referred from Jalisco.…”
Section: Discussioncontrasting
confidence: 64%